Internalisasi Nilai Jaizah Sebagai Instrumen Pelayanan dalam Meningkatkan Okupansi Hotel Syariah - Muh Munafri S; Muslimin Kara; Abdul Wahid Haddade; Ruslang Ruslang (Al-Azhar Journal of Islamic Economics, 2023)
The hotel business, especially sharia hotels, requires a service value to guests and customers that comes from Islamic teachings as an instrument in increasing occupancy. One of the values of Islamic guest services that can accommodate this is the value of jaizah. This study aims to determine how the implementation and internalization of Islamic guest and customer service values, especially the value of jaizah in increasing sharia hotel occupancy. This research is a field research with qualitative descriptive analytical method. The results of this study indicate that with the implementation and internalization of Islamic guest and customer service values, especially the jaizah value in sharia hotels, in this case Khas Makassar Hotel (KMH) has a very significant influence in increasing hotel occupancy. Based on the results of these studies, the value of this jaizah should be recommended to be applied to the hotel business as an instrument in increasing the occupancy of sharia hotels and also conventional hotels.